2016
DOI: 10.4103/2277-9175.175902
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of splinting and splinting plus local steroid injection in severe carpal tunnel syndrome: A Randomized control clinical trial

Abstract: Background:The Study aimed to compare the effectiveness of two commonly used conservative treatments, splinting and local steroid injection in improving clinical and nerve conduction findings of the patients with severe carpal tunnel syndrome (CTS).Materials and Methods:In this randomized control clinical trial, the patients with severe CTS selected and randomized in two interventional groups. Group A was prescribed to use full time neutral wrist splint and group B was injected with 40 mg Depo-Medrol and presc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
3
3
0
Order By: Relevance
“…Also, the mean difference of FSS from baseline to the 12th week after treatment was significantly higher in Group B. Our study results were similar to the reported results of Khosrawi et al [16].…”
Section: Discussionsupporting
confidence: 92%
“…Also, the mean difference of FSS from baseline to the 12th week after treatment was significantly higher in Group B. Our study results were similar to the reported results of Khosrawi et al [16].…”
Section: Discussionsupporting
confidence: 92%
“…The symptoms and functional status improved significantly, though the symptoms got better greatly. The data of other researches were mostly in favor of our results [3,5,7,13,14,16,17]. Our study showed that patients who used splint had meaningful enhancement in both the symptoms and functional scores, while the others who had no treatment only showed enhancement in their symptoms.…”
Section: Hui Et Al Demonstrated That Open Carpal Tunnel Re-supporting
confidence: 44%
“…Another study by Khosravi et al compared the effectiveness of steroid injection versus steroid injection plus splinting in severe CTS. Their results showed significant improvement of functional scale, patient satisfaction, and nerve conduction parameters after 4 weeks in both groups [14].…”
Section: Hui Et Al Demonstrated That Open Carpal Tunnel Re-mentioning
confidence: 93%
“…[ 35 , 36 ] In many randomized controlled studies, a splint is used as a control group treatment. [ 37 , 38 ] In this study, which we conducted to evaluate the effectiveness of active underwater pulsed US therapy more clearly, we administered splints to all groups, and an improvement was observed in VAS, clinical assessment parameters, HGS, and PQAS in all groups. However, as other treatment types were also administered to two groups in addition to splinting, we could not attribute the success only to the splint alone.…”
Section: Discussionmentioning
confidence: 99%